Pauline slave welfare in historical context: an equality analysis - Thompson, W. H. Paul (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2023)
"W. H. Paul Thompson engages in an equality analysis of Pauline ethics on slave welfare--how slaves should be treated in comparison to free persons. He reconstructs a distinctive Jewish numerically equal treatment ethic for slaves and free persons which Paul reorients into a Christocentric framework."--Cover page 4